The antiepileptic drug oxcarbazepine inhibits the growth of patient-derived isocitrate dehydrogenase mutant glioma stem-like cells - Dao Trong, Huy Philip; Jungwirth, Gerhard; Unterberg, Andreas; Herold-Mende, Christel; Warta, Rolf (Cells, 2023)
Patients diagnosed with isocitrate dehydrogenase mutant (IDHmut) gliomas suffer frequently from seizures. Although the clinical course is less aggressive than that of its IDH wildtype counterpart, recent discoveries have shown that epileptic activity can promote tumor proliferation. However, it is not known if antiepileptic drugs confer additional value by inhibiting tumor growth. In this study, the antineoplastic properties of 20 FDA-approved antiepileptic drugs (AEDs) were tested in six patient-derived IDHmut glioma stem-like cells (GSCs). Cell proliferation was assessed using the CellTiterGlo-3D assay. Two of the screened drugs (oxcarbazepine and perampanel) demonstrated an antiproliferative effect. A subsequent eight-point dose-response curve proved the dose-dependent growth inhibition for both drugs, but only oxcarbazepine reached an IC50 value below 100 µM in 5/6 GSCs (mean 44.7 µM; range 17.4-98.0 µM), approximating the possible cmax for oxcarbazepine in patient serums. Furthermore, the treated GSC spheroids were 82% smaller (mean volume 1.6 nL vs. 8.7 nL; p = 0.01 (live/deadTM fluorescence staining)), and the apoptotic events increased by more than 50% (caspase-3/7 activity; p = 0.006). Taken together, this drug screen of a large series of antiepileptic drugs identified oxcarbazepine as a potent proapoptotic drug in IDHmut GSCs, which combines antiepileptic and antineoplastic properties to treat this seizure-prone patient population.